Review on Early Detection of Alzheimer’s Disease using Neuroimaging Techniques - N, Vishnu; Vaidya, Rachana R; N, Chaitra; P, Srinidhi S; B, Shreyas (Perspectives in Communication, Embedded-systems and Signal-processing - PiCES, 2021)
Alzheimer’s disease (AD) is the most common form of dementia. AD begins slowly, where it first involves a part of the brain that controls thought, memory, and language. Names and incidents are things that initial stage AD patients have a hard time remembering. Early detection of AD is very crucial for further aid and treatment. This paper presents a review and analysis of the different methods employed to detect AD or mild cognitive impairment (MCI). Machine learning, neuroimaging, and deep learning neural networks are few of the techniques which are compared and analysed based on their performance and accuracy. Each model is critically analysed and provided with limitations, advantages, and best application.